1992
DOI: 10.1152/jn.1992.67.6.1633
|View full text |Cite
|
Sign up to set email alerts
|

APB suppresses synaptic input to retinal horizontal cells in fish: a direct action on horizontal cells modulated by intracellular pH

Abstract: 1. Membrane potentials and cone-driven light responses were recorded from the H1-type horizontal cells in isolated retinas. Membrane potentials and intracellular pH were recorded also in enzymatically dissociated solitary horizontal cells. 2. In isolated retinas the glutamate analogue 2-amino-4-phosphonobutyrate (APB) hyperpolarized horizontal cells and reduced their light responses in a dose-dependent manner (5-200 microM). 3. The action of APB depended on the formulation of the saline; APB was effective in L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…On the other hand, from similar investigations in goldfish retina, Nawy et al (1989) reported that APB could suppress the transmission from cones to horizontal cells, and Takahashi and Copenhagen (1992) have recently demonstrated a direct action of APB on isolated goldfish horizontal cells. From these results, one would expect expression of a metabotropic receptor where APB has high potency, e.g.…”
Section: Horizontal Cellsmentioning
confidence: 91%
“…On the other hand, from similar investigations in goldfish retina, Nawy et al (1989) reported that APB could suppress the transmission from cones to horizontal cells, and Takahashi and Copenhagen (1992) have recently demonstrated a direct action of APB on isolated goldfish horizontal cells. From these results, one would expect expression of a metabotropic receptor where APB has high potency, e.g.…”
Section: Horizontal Cellsmentioning
confidence: 91%
“…APB is a highly selective competitive antagonist at the mGluR6 receptor that localizes exclusively at the metabotropic G-proteincoupled synapse between rod and cone photoreceptors and their respective DBCs (Shiells et al 1981;Slaughter and Miller 1981). APB does not act at the chemical synapse onto HBCs, although it may alter horizontal feedback onto photoreceptors in some preparations (Hare and Owen 1992;Nawy et al 1989;Takahashi and Copenhagen 1992;Yang and Wu 1989).…”
Section: Rapid-on/off Stimuli Elicit Complex Primate Erg Originsmentioning
confidence: 99%
“…APB has been reported to antagonize the horizontal cell response to light (Nawy et al, 1989). This action could be caused by a presynaptic depression of transmitter release by photoreceptors, an antagonist effect on horizontal cell AMPA/kainate GluRs, or a modulation of these receptors or some other conductance through a second messenger pathway activated by APB and/or ACPD (Yang and Wu, 1991;Takahashi and Copenhagen, 1992).…”
Section: Metabotropic Glutamate Receptors In Retinamentioning
confidence: 99%